DESIGN OF INFORMATION SYSTEMS AND COMPUTER SALES COMPUTER ACCESSORIES ASSEMBLY IN. BILLY MOON USING VISUAL FoxPro 9.0 - Billy Hardianto Wibowo; Elly Agustina J.,S.Kom.,MMSI (Jurnal Sistem Informasi, 2010)
Sales of Computer Information Systems and Computer Assembled Accecories, is onevery important part in a company, particularly those engaged in trade. Because inactivities jualbeli transaction. Transparency and accuracy of the information isneeded, especially in improve the quality of service to the customer. previous systemof sales at PT. BILLY MOON, things are still done manually. So well many of thediscovery of several problems. Besides, it also slows the quality service. Therefore,an improvement requires the computerized system. In order to facilitate all activitieswithin the company. Like, data processing well, record keeping, preparation ofreports and others. In this case, given that dperlukannya a system improvement. Thenauthors propose an Information System Design of Sales at PT. BILLY MOON. Inorder for information and service needs of the customer, can be improved. Indesigning this sales system, the author uses the Microsoft Visual FoxPro 9.0.